EFFECT OF THE ALOPPURINOL IN THE VIABILITY OF IN VITRO HEPATOCYTES MURINE - Ferreira, Sandra Maria; Nicoluzzi, João Eduardo Leal; Repka, João Carlos Domingues; Aita, Carlos Alberto Mayora; Alves, Carlos Fernandes (Brazilian Journal of Transplantation, 2007)
Purpose: The purpose of this work was to observe the protective effect of the allopurinol on the hepatocytes in culture by its inhibitor effect of the xanthine oxidase in generating oxygen-free radicals. Methods: Hepatocytes have been isolated from the liver of rats by enzymatic dissociation, according to technique described on 1969 and modified on 1976. Surgical techniques were performed in the experimental operation room of PUC/PR. It were performed initial counting, and the feasibility was calculated using the exclusion test by Trypan blue. The albumin and malondyaldeide concentrations were analyzed using biochemical colorimetric tests. Results: The outcome of isolated hepatocytes after enzymatic digestion using colagenase was 1.5X106 cel/gr/liver for CG, and 1.7 X106 cel/gr/liver for SG, with initial 60% feasibility for both groups. The outcome for albumin was of 0.1868 mg/ml (± 0.023) for CG, and 0.1384 mg/ml (± 0.019) for SG. For the malondyaldeide, results were 0.3963 nmol/mg proteins (± 0.0 98) for CG, and 0.2040 nmol/mg proteins (+-0.058) for SG. Conclusion: Allopurinol reduces the production of malondyaldeide, showing lower oxidizer stress in cells previously treated with that medication. But such reduction is not enough to interfere in the support of the cellular feasibility.